Metatranscriptomic Analysis of Corals Inoculated With Tolerant and Non-Tolerant Symbiont Exposed to High Temperature and Light Stress - Yuyama, Ikuko; Higuchi, Tomihiko; Mezaki, Takuma; Tashiro, Hisako; Ikeo, Kazuho (Frontiers in Physiology, 2022)
Algal symbionts of corals can influence host stress resistance; for example, in the Pacific Ocean, whereas Cladocopium (C-type) is generally dominant in corals, Durusdinium (D-type) is found in more heat-resistant corals. Thus, the presence of D-type symbiont likely increases coral heat tolerance, and this symbiotic relationship potentially provides a hint to increase the stress tolerance of coral–algal symbioses. In this study, transcriptome profiles of Cladocopium- and Durusdinium-harboring Acropora solitaryensis (C-coral and D-coral, respectively) and algal photosystem functioning (Fv/Fm) under bleaching conditions (high temperature and light stress) were compared. Stress treatment caused algal photoinhibition that the Fv/Fm value of Symbiodiniaceae was immediately reduced. The transcriptome analysis of corals revealed that genes involved in the following processes were detected: endoplasmic reticulum (ER) stress, mitophagy, apoptosis, endocytosis, metabolic processes (acetyl-CoA, chitin metabolic processes, etc.), and the PI3K-AKT pathway were upregulated, while DNA replication and the calcium signaling pathway were downregulated in both C- and D-corals. These results suggest that unrepaired DNA and protein damages were accumulated in corals under high temperature and light stress. Additionally, some differentially expressed genes (DEGs) were specific to C- or D-corals, which includes genes involved in transient receptor potential (TRP) channels and vitamin B metabolic processes. Algal transcriptome analysis showed the increased expression of gene encoding photosystem and molecular chaperone especially in D-type symbiont. The transcriptome data imply a possible difference in the stress reactions on C-type and D-type symbionts. The results reveal the basic process of coral heat/light stress response and symbiont-type-specific coral transcriptional responses, which provides a perspective on the mechanisms that cause differences in coral stress tolerance.